Economic burden of silent mental disorders: a case study of agnosia in schizophrenia - Chattu, Vijay Kumar; Mahon, Paula (International Journal Of Community Medicine And Public Health, 2017)
Mental health problems affect society as a whole, and not just a small, isolated segment. In developed countries with well-organized healthcare systems, between 44% and 70% of patients with mental disorders do not receive treatment whereas in developing countries the treatment gap being close to 90%. Schizophrenia is a severe mental disorder affecting more than 21 million people worldwide. People with schizophrenia are 2-2.5 times more likely to die early than the general population. The case study highlights about agnosia in a schizophrenic patient in a primary care setting and how to address the management at a broader perspective using the appropriate antipsychotic medication and ensuring the support from a family without violating the human rights of the patient. The World Economic Forum estimated that the cumulative global impact of mental disorders in terms of lost economic output will amount to US 16 trillion over the next 20 years, equivalent to more than 1% of the global gross domestic product. Mental health should be a concern for all of us, rather than only for those who suffer from a mental disorder. The mental health action plan 2013-2020, endorsed by the World Health Assembly in 2013, highlights the steps required to provide appropriate services for people with mental disorders including schizophrenia. A key recommendation of the action plan is to shift services from institutions to the community. Mental health must be considered a focus of renewed investment not just in terms of human development and dignity but also in terms of social and economic development.